Etiologic Causes and Epidemiological Characteristics of Patients with Intraocular Foreign Bodies: Retrospective Analysis of 1340 Cases over Ten Years - Lin Li; Hai Lu; Kai Ma; Yun-Yun Li; Hai-Yan Wang; Ning-Pu Liu (Journal of Ophthalmology)
Objective. Patients with intraocular foreign bodies were retrospectively analyzed. Population characteristics, pathogenic factors, and the outcomes during the past ten years were discussed. Design. Retrospective case series study. Method. Medical records of 1340 patients hospitalized in Beijing Tongren Hospital from January 1, 2004, to December 31, 2013, were collected. Results. Average age was 33.0 ± 13.8 (1–76) years old in 1340 patients. There were more males (1270, 94.8%) than females (70, 5.2%). Patients from outside of Beijing (82.1%, n=1100) prevailed. Farmers (32.1%, n=430) and workers (22.3%, n=299) were the top two affected professions. Leading two causes were splashing of foreign bodies (SFB) (58.6%, n=785) and explosives (31.8%, n=426). More males than females were injured by SFB (59.4% versus 44.3%, P=0.009). Firework injury was the commonest (41.6% versus 3.1%–15.3%, P<0.05) in patients under nine. The annual percentages in patients over 50 increased (P<0.001) and in patients by explosives decreased (P=0.027). Conclusion. Most patients in this study were young males from outside of Beijing and farmers. SFB accounted most for patients over 10 years old and fireworks for those under ten. Patients over 50 increased while those by explosives decreased annually over the period.